Improving leadership effectiveness by enhancing spiritual and emotional intelligence: an empirical investigation in Asia - Aahad, M. Osman-Gani; Kiyoshi, Kobayashi; Kabir, Sardar Md Humayun (2018)
Leadership effectiveness is impacted by multiple intelligences of individuals who have relevant competencies. Spiritual intelligence and emotional intelligence are two such important competencies that resultineffective leadership. Each competency has a set of skills dimensions associated with it. Previous researchers have emphasized the necessity and importance of spiritual intelligence and emotional intelligence for individuals, but very few studieshave empirically examined the effects of these competencies on effective leadership. Enhancement of the relevant lacking dimensions of spiritual and emotional intelligence is of utmost importancefor improvingleadership effectiveness. This study investigated the impacts of spiritual and emotional intelligence dimensions for improvingleadership effectiveness in contemporarybusiness organizations of Asia. Data was collected from 502 employees working in varioustypes of organizations operating in Peninsular Malaysia. Structural equation modeling approach was used for analyzing the data and it was found that employees’ spiritual intelligence and emotional intelligence dimensions havesignificantpositive impacts on leadership effectiveness. The empirical evidence obtained from this study would make significant contributions in advancing the current knowledge of leadership development. Particularly, HRD theories and practices would be enriched through the identification and application of appropriate leadership development strategies. The findings may also help in developing new leadership assessment tools, designing appropriate interventions andin developing leadership effectiveness indices. Implications of the findings for future research andfor professional practice are discussed at the end of this paper.